Comparative study of polycaprolactone electrospun fibers and casting films enriched with carbon and nitrogen sources and their potential use in water bioremediation - Alejandra Pompa-Monroy, Daniella; Leticia Iglesias, Ana; Gulam Dastager, Syed; Namdeo Thorat, Meghana; Olivas-Sarabia, Amelia; Valdez-Castro, Ricardo; Angelica Hurtado-Ayala, Lilia; Manuel Cornejo-Bravo, Jose; Lizeth Perez-Gonzalez, Graciela; Jesus Villarreal-Gomez, Luis (Membranes, 2022)
Augmenting bacterial growth is of great interest to the biotechnological industry. Hence, the effect of poly (caprolactone) fibrous scaffolds to promote the growth of different bacterial strains of biological and industrial interest was evaluated. Furthermore, different types of carbon (glucose, fructose, lactose and galactose) and nitrogen sources (yeast extract, glycine, peptone and urea) were added to the scaffold to determinate their influence in bacterial growth. Bacterial growth was observed by scanning electron microscopy; thermal characteristics were also evaluated; bacterial cell growth was measured by ultraviolet-visible spectrophotometry at 600-nm. Fibers produced have an average diameter between 313 to 766 nm, with 44% superficial porosity of the scaffolds, a glass transition around similar to 64 degrees C and a critical temperature of similar to 338 degrees C. The fibrous scaffold increased the cell growth of Escherichia coli by 23% at 72 h, while Pseudomonas aeruginosa and Staphylococcus aureus increased by 36% and 95% respectively at 48 h, when compared to the normal growth of their respective bacterial cultures. However, no significant difference in bacterial growth between the scaffolds and the casted films could be observed. Cell growth depended on a combination of several factors: type of bacteria, carbon or nitrogen sources, casted films or 3D scaffolds. Microscopy showed traces of a biofilm formation around 3 h in culture of P. aeruginosa. Water bioremediation studies showed that P. aeruginosa on poly (caprolactone)/Glucose fibers was effective in removing 87% of chromium in 8 h.
Keywords: bacterial growth; carbon source; electrospinning; nitrogen source; poly (caprolactone)